Structural design of a lattice pykrete tower. (June 2022) - Pronk, Arno; Mergny, Elke; Li, Qingpeng
Abstract: Pykrete is a material used for temporary structures in cold environments. In the last decade, this material has generally been used in shell structures that were constructed using inflatable fabric formwork and ropes. Recently, research has been carried out to use pykrete in structures made of linear elements and some structures of low heights have been able to be built. A pykrete tower-like structure was built in 2019 for the International Ice and Snow Innovation Design and Construction competition, based on a proposal made by the Eindhoven University of Technology. This structure raised to 11 m, making it the tallest pykrete structure with linear elements built so far. This paper describes the base concepts, design process, testing methodology and building methods of this tower.